DEVELOPING PROCESS GENRE - BASED APPROACH HANDOUT FOR TEACHING WRITING OF EXPOSITION HORTATORY TEXT FOR SENIOR HIGH SCHOOL STUDENTS - Handayani Handayani; Jufrizal Jufrizal; Hamzah Hamzah (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2018)
This article is a development research that aims to develop teaching-based writing materials in the process of producing a genre in the form of exposition hortatory. In this study also estimated the level of validity, practicality and effectiveness of teaching materials developed. This research method is done in four stages; definition, design, development and limited deployment; on the students of grade XI IPA 2 SMA Adabiah Padang. After the stages of dissemination is limited, measured product practicability and product effectiveness to the value of student writing. Development results show the validity of the product contained in the category can be used with the improvement with a value of 77.4. Practicality of the product is stated at the value of 88.77 and the effectiveness at the value of 80%. It can be concluded that the product can be used as teaching teaching material.